2021
DOI: 10.33776/et.v11i1.5137
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Ambassadors as Special Destination Image Inducers

Abstract: The image of destinations is a key factor when it comes to positioning and attracting the attention and interest of potential tourists. That being, the subject matter is relevant to experts and academics as well as destination managers looking for new alternatives to generate greater impact and influence. Today, the use of information and communication technologies (ICT) is widespread in all areas of life, being also useful and fully adopted in tourism image projections, mainly through social networks. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…As a result, the destination image becomes an available resource for self-expression ( Elliott and Wattanasuwan, 1998 ) and an extension of self ( Belk, 1988 ). Morand et al (2021) also highlight the influence of tourism ambassadors as destination image inducers within the online realm. In other words, in the social media environment, destination symbolism significantly changes tourists’ attitudes.…”
Section: Introductionmentioning
confidence: 89%
“…As a result, the destination image becomes an available resource for self-expression ( Elliott and Wattanasuwan, 1998 ) and an extension of self ( Belk, 1988 ). Morand et al (2021) also highlight the influence of tourism ambassadors as destination image inducers within the online realm. In other words, in the social media environment, destination symbolism significantly changes tourists’ attitudes.…”
Section: Introductionmentioning
confidence: 89%
“…Concerning destination image/brand image and according to [33], the image of the tourism destination is an important variable to consider in the planning, management, and promotion of a destination because it represents an overall impression of the destination or, to be more precise, a set of impressions and feelings about it. Some authors [65,66] have identified two types of tourism destination images: organic and induced/projected [65]. The organic image is created from non-commercial sources and is formed by the cultural component, that is, by general knowledge and by friends' information.…”
Section: Sustainable Marketing and Projected Destination Imagementioning
confidence: 99%
“…The organic image is created from non-commercial sources and is formed by the cultural component, that is, by general knowledge and by friends' information. The induced/projected destination image differs from the organic one since it is formed when the tourist seeks information voluntarily or it is submitted to any available commercial sources of information that stakeholders promote through the most diverse means [65][66][67]. These authors argue that when we analyze induced/projected destination images/brand images, we are facing destination imagery that they define as a "momentary processes of storage and retrieval of information from memory upon receiving destination stimuli and resulting in holistic perceptions of a destination" [33] (p. 85).…”
Section: Sustainable Marketing and Projected Destination Imagementioning
confidence: 99%
“…2015) andZhao et al (2015) similarly highlight the importance of expertise factors in adopting UGC and online travel Morand et al (2021). also highlight the influence of tourism ambassadors as destination image inducers within the online realm.…”
mentioning
confidence: 93%
“…The increase in social media usage reflects how consumers depends on UGC to search out travel information. Recent studies propose that tourists' personal experiences and exposure, amplified by social media's emotional contagion and information dissemination, can substantially impact their travel views, intentions, and future behaviour (Aryani et al, 2018;Manap & Adzharudin, 2013;Morand et al, 2021;Nguyen, 2020). Besides, it is essential to understand the changes on/from the demand side, as proposed by various researchers such as Nair and Sinha (2020), , Kour et al (2020) and Zenker and Kock (2020).…”
Section: Introductionmentioning
confidence: 99%